Strategic development: how to open the 'black box'of strategic planning - Salinas O., Jose (1999)
The strategy-making process, for Henry Mintzberg and others, is seen as an impenetrable 'black box' for planners, around which they work, providing some of its inputs, programming its outputs as well as encouraging strategic thinking in general. The challenge is how to open this 'black box' to generate creative and doable strategies, to evaluate them and choose the most favorable for the company.   The Strategic Decisions Group (SDG) process allows to generate alternative strategies; which are evaluated given the relevant information and the c/early established decision criteria to determine the potential value and risk associated with each strategy. This process is efficient and well balanced; it does not waste time and resources in issues that are not crucial to the decisions that define the strategy, concluded in a timing manner and tend to 100% of quality on the content of the decision, and assure a commitment for its implementation. The success of this systematic process, with intermediate reviews, hinges on two main factors: having the right people involved and ensuring deliverables associated with the elements of the decision quality at the end of each step.